2019
DOI: 10.1002/ehf2.12442
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐encoded magnetic resonance: a method for the assessment of myocardial deformation

Abstract: This study aims to assess the usefulness of strain‐encoded magnetic resonance (SENC) for the quantification of myocardial deformation (‘strain’) in healthy volunteers and for the diagnostic workup of patients with different cardiovascular pathologies. SENC was initially described in the year 2001. Since then, the SENC sequence has undergone several technical developments, aiming at the detection of strain during single‐heartbeat acquisitions (fast‐SENC). Experimental and clinical studies that used SENC and fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 90 publications
(157 reference statements)
0
38
0
Order By: Relevance
“…An advanced strain-encoded (SENC and fast-SENC) CMR tagging technology provides high accuracy and reproducibility during single heartbeat acquisitions without contrast and may be helpful in the future to detect early cardiotoxicity. 142 The PROACT study with mixed blinded and unblinded design will include breast cancer, lymphoma and sarcoma patients receiving AC chemotherapy, also aiming to initiate cardioprotection at the earliest possible moment (Figures 7 and 8). 143 Also, a decrease of native T1 times as early as 48 h after the first AC cycle has been shown to predict the development of CTRCD after completion of chemotherapy.…”
Section: Future Directions and Imaging Technologiesmentioning
confidence: 99%
“…An advanced strain-encoded (SENC and fast-SENC) CMR tagging technology provides high accuracy and reproducibility during single heartbeat acquisitions without contrast and may be helpful in the future to detect early cardiotoxicity. 142 The PROACT study with mixed blinded and unblinded design will include breast cancer, lymphoma and sarcoma patients receiving AC chemotherapy, also aiming to initiate cardioprotection at the earliest possible moment (Figures 7 and 8). 143 Also, a decrease of native T1 times as early as 48 h after the first AC cycle has been shown to predict the development of CTRCD after completion of chemotherapy.…”
Section: Future Directions and Imaging Technologiesmentioning
confidence: 99%
“…Furthermore, a recent study by Lapinskas et al demonstrated feasibility of fast‐SENC to assess LV volumes and LVEF, making it a convenient option for functional assessment of the heart. Such short acquisition and post‐processing times make fast‐SENC technique very attractive in daily routine, especially in severely ill patients and children . It must be noted that due to technical limitations, radial strain cannot be assessed from SENC acquisitions .…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that due to technical limitations, radial strain cannot be assessed from SENC acquisitions . Additionally, it has a worse spatial resolution than TAG and FT . On the other end of the spectrum, FT is a post‐processing technique that does not require additional image acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating the ICM from the NICM is of paramount importance due to the different prognosis and treatment strategies. 4,6 Coronary angiography is a gold standard method to diagnose the CAD. Despite its routine use in the clinical practice, it is time requirements, radiation load, and periprocedural complications that make it a complex examination with strict indications.…”
Section: Discussionmentioning
confidence: 99%
“…5 Regarding prognosis and different therapeutic approaches, HF aetiology is usually specified with cardiac magnetic resonance (CMR), computed tomography, or invasive coronary angiography. [6][7][8] The 3D STE with its capability to analyse the myocardial mechanics is a cost-effective imaging modality. Its applicability and clinical relevance in the differentiation between ischaemic and non-ischaemic cardiomyopathy (NICM) lack sufficient data.…”
Section: Introductionmentioning
confidence: 99%